Effect of Post-Printing Cooling Conditions on the Properties of ULTEM Printed Parts - Glaskova-Kuzmina, Tatjana; Dejus, Didzis; Jatnieks, Janis; Aniskevich, Andrey; Sevcenko, Jevgenijs; Sarakovskis, Anatolijs; Zolotarjovs, Aleksejs (MDPI, 2023)
first_pageDownload PDFsettingsOrder Article Reprints Open AccessArticle Effect of Post-Printing Cooling Conditions on the Properties of ULTEM Printed Parts by Tatjana Glaskova-Kuzmina 1,2,*ORCID,Didzis Dejus 1,Jānis Jātnieks 1,Andrey Aniskevich 2ORCID,Jevgenijs Sevcenko 2,Anatolijs Sarakovskis 3 andAleksejs Zolotarjovs 3 1 Baltic3D.eu, Braslas 22D, LV-1035 Riga, Latvia 2 Institute for Mechanics of Materials, University of Latvia, Jelgavas 3, LV-1004 Riga, Latvia 3 Institute of Solid State Physics, Kengaraga 8, LV-1063 Riga, Latvia * Author to whom correspondence should be addressed. Polymers 2023, 15(2), 324; https://doi.org/10.3390/polym15020324 Submission received: 24 November 2022 / Revised: 29 December 2022 / Accepted: 6 January 2023 / Published: 8 January 2023 (This article belongs to the Special Issue Mechanical and Physical Properties of 3D Printed Polymer Materials) Downloadkeyboard_arrow_down Browse Figures Review Reports Versions Notes Abstract This paper aimed to estimate the effect of post-printing cooling conditions on the tensile and thermophysical properties of ULTEM® 9085 printed parts processed by fused deposition modeling (FDM). Three different cooling conditions were applied after printing Ultem samples: from 180 °C to room temperature (RT) for 4 h in the printer (P), rapid removal from the printer and cooling from 200 °C to RT for 4 h in the oven (O), and cooling at RT (R). Tensile tests and dynamic mechanical thermal analysis (DMTA) were carried out on samples printed in three orthogonal planes to investigate the effect of the post-printing cooling conditions on their mechanical and thermophysical properties. Optical microscopy was employed to relate the corresponding macrostructure to the mechanical performance of the material. The results obtained showed almost no difference between samples cooled either in the printer or oven and a notable difference for samples cooled at room temperature. Moreover, the lowest mechanical performance and sensitivity to the thermal cooling conditions were defined for the Z printing direction due to anisotropic nature of FDM and debonding among layers.--//-- This is an open access article Glaskova-Kuzmina, T.; Dejus, D.; Jātnieks, J.; Aniskevich, A.; Sevcenko, J.; Sarakovskis, A.; Zolotarjovs, A. Effect of Post-Printing Cooling Conditions on the Properties of ULTEM Printed Parts. Polymers 2023, 15, 324. https://doi.org/10.3390/polym15020324 published under the CC BY 4.0 licence.
This research was funded by the European Regional Development Fund within Measure 1.1.1.1 “Industry-Driven Research” of the Specific aid objective 1.1.1 “To increase the research and in-novation capacity of scientific institutions of Latvia and their ability to attract external funding by investing in human resources and infrastructure” of the Operational Program “Growth and Employment” (Project No. 1.1.1.1/20/A/188). A.A. and J.S. are grateful for funding received from ERDF Project No. 1.1.1.1/19/A/031 “OPTITOOL, Decision Tool for Optimal Design of Smart Polymer Nanocomposite Structures Produced by 3D Printing”. A.S. and A.Z. are grateful for funding received from the European Union Horizon 2020 Framework program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; ULTEM; fused deposition modelling; thermal history; cooling conditions; mechanical properties; thermophysical properties